Influence of the initial state of ZrO2 on genesis, activity and stability of Ni/ZrO2 catalysts for steam reforming of glycerol - Omarov Shamil O.; Sladkovskiy Dmitry; Martinson Kirill Dmitrievich; Peurla Markus; Aho Atte; Murzin Dmitry; Popkov Vadim Igorevich (Elsevier B.V., 2022)
The effect of the initial state of ZrO2 on properties of Ni/ZrO2 catalysts for hydrogen production in steam reforming of glycerol was investigated. The catalysts were synthesized by impregnating the supports obtained by varying the  treatment temperature of  ZrO2‧nH2O  and  introducing Y2O3 as  a  promoter. All  materials were characterized by thermal analysis, X-ray diffraction, N2 physisorption, scanning electron microscopy, H2-TPR, NH3-TPD and transmission electron microscopy. The mutual influence of NiO and ZrO2 on the genesis of the phase composition, pore structure and reducibility was demonstrated. Different catalytic behavior is explained by influence of the initial form of the support on the size, morphology of Ni particles, and the support thermal stability. The initial activity of Ni/ZrO2is proportional to the monoclinic phase content. The catalysts based on tetragonal ZrO2 displayed the best stability. For the first time, the presence of the aldol condensation products in glycerol steam reforming was demonstrated